Lanthanide distribution in some doped alkaline earth aluminates and gallates - Saines, P; Elcombe, M; Kennedy, B (2006)
High-resolution neutron and synchrotron X-ray powder diffraction studies are reported for the six oxides AB2O4 (A=Ca2+, Sr2+ and Ba2+ and B=Al3+ and Ga3+). These oxides all adopt a stuffed tridymite type structure, the precise nature of which depends on both the A- and B-type cations. Bond valence calculations reveal a range of values for the various A-type cations, in all cases at least one site is significantly underbonded. Conversely the tetrahedral B-type sites invariably exhibit unexceptional bond valencies. Attempts to dope the oxides with various lanthanides to the 1% level invariably resulted in some segregation into alternate phases located at the grain boundaries. The identity of the impurity phases is presented and the importance of bond valencies in understanding this segregation is highlighted.